Double-sided moral hazard in job displacement insurance contracts - Donald O. Parsons (Institute for the Study of Labor (IZA), 2011)
Job displacement insurance typically includes both unemployment benefits and lump-sum severance pay, and each has provoked policy concerns. Unemployment insurance concerns have centered on distorted job search/offer acceptance decisions by the worker, severance-induced firing cost concerns on excessive labor hoarding by firms. A single period private contracting model is used to investigate the interaction of these two seemingly distinct issues. Viewed singly, familiar results emerge. The absence of separation benefits of any kind leads to excessive labor hoarding as a primitive form of earnings insurance. In a limited information environment, the distribution of job displacement insurance between the two benefit types becomes important. Unemployment insurance benefits must be limited (relative to first-best levels) and severance pay made more generous. Firing cost considerations are less familiar. Because the firm wants to provide benefits, they cannot be contracted around. Although formally driven by the sum of (unsubsidized) severance pay and expected unemployment benefits, the second-best firing cost program limits severance pay only. Together the two constraints create an unpromising contracting environment. The firing cost constraint is the more easily relaxed by government action - subsidies of sufficient size to one or another of the separation programs will work. Offer acceptance requires restrictions on leisure (workfare). Unfortunately, if first-best benefits are mandated, efficiency requires that both be eased.
urn:nbn:de:101:1-201110263414
Keywords: J65; J41; J33; J08; 330; job displacement; unemployment insurance; severance pay; moral hazard; firing costs; Kündigung; Kosten; Arbeitslosenversicherung; Lohn; Betriebszugehörigkeit; Moral Hazard; Unterbeschäftigung; Theorie